GAGASAN PEMBENTUKAN LAPAS KHUSUS NARKOTIKA DI PROVINSI RIAU MENURUT KLASIFIKASI KEJAHATAN DIKAITKAN DENGAN TUJUAN PEMIDANAAN - Isfardy Isfardy (Jurnal Ilmu Hukum, 2018)
Establishment of Special Drugs LAPAS in Riau Province according to crime classification is related to the purpose of punishment, which is done to see the condition of guidance to the Prisoners of Correctional Institution in Penitentiary in Riau Province which can be said not run maximally. This is evidenced by the limited facilities and infrastructure of visitation program guidance, the state of LAPAS is over-capacity, because all convicts of general and special crime are combined, so there is no separation wall. This is a concern given the many more drug users who are in the LAPAS, because between drug dealers, drug dealers and couriers into a single cell in prison. The purpose of punishment that had made the deterrent effect of the offender became not realized, because the coaching system that is in the LAPAS cannot run optimally. Constraints in fulfilling the idea of formation of special narcotic Drugs in Riau Province according to crime classification is associated with the purpose of punishment include: a. Maturity or mental readiness of personnel or prison officers, because there have been many violations committed by LAPAS officers in regulating the circulation of narcotics in prison. b. The absence of response from the Riau Provincial Government to over capacity of LAPAS in Riau Province so that there is no pressure to the Department of Law and Human Rights Department to immediately build a special LAPAS for Narcotics Prisoners. c. The realization of the Ministry of Justice and Human Rights was cut off in the middle of the road, since 2016, the discourse to build a special LAPAS for Narcotics Prisoners has been echoed, but until now, the realization has never materialized, even though the Ministry of Justice and Human Rights already have 5, 8.